Insights into the Progression of Labile Hb A1c to Stable Hb A1cvia a Mechanistic Assessment of 2, 3-Bisphosphoglycerate Facilitation of the Slow Nonenzymatic Glycation Process. (2nd January 2019) - Mottishaw, Christina R.; Becker, Stephanie; Smith, Brandy; Titus, Gentry; Holman, R.W.; Rodnick, Kenneth J.
Abstract: Nonenzymatic glycation (NEG) of human hemoglobin (Hb A) consists of initial non covalent, reversible steps involving glucose and amino acid residues, which may also involve effector reagent(s) in the formation of labile Hb A1c (the conjugate acid of the Schiff base). Labile Hb A1c can then undergo slow, largely irreversible, formation of stable Hb A1c (the Amadori product). Stable Hb A1c is measured to assess diabetic progression after labile Hb A1c removal. This study aimed to increase the understanding of the distinctions between labile and stable Hb A1c from a mechanistic perspective in the presence of 2, 3-bisphosphoglycerate (2, 3-BPG). 2, 3-Bisphosphoglycerate is an effector reagent that reversibly binds in the Hb A1c pocket and modestly enhances overall NEG rate. The deprotonation of C2 on labile Hb A1c in the formation of the Amadori product was previously proposed to be rate-limiting. Computational chemistry was used here to identify the mechanism(s) by which 2, 3-BPG facilitates the deprotonation of C2 on labile Hb A1c . 2, 3-Bisphosphoglycerate is capable of abstracting protons on C2 and the α-nitrogen of labile Hb A1c and can also deprotonate water and/or amino acid residues, therefore preparing these secondary reagents to deprotonate labile Hb A1c . Parallel reactions not leading to an Amadori product were found that include formation of the neutral Schiff base, dissociation of glucose from the protein, and cyclic glycosylamine formation. These heretofore under appreciated parallel reactions may help explain both the selective removal of labile from stable Hb A1c and the slow rate of NEG.